The Role of Loan Loss Provisions in Competition Toward Bank Stability - Fath Mala, Chajar Matari (Dinasti Publisher, 2024)
This study investigates how competition and loan loss provisions (LLP) affect stability by including the variable of LLP as a moderating factor introduced as a new variable in the research framework. This study used panel data from 2012 to 2021 from Indonesia's largest banks by assets. This study will analyze competitiveness, loan loss provision, and stability using moderated regression. This study determined long-term and short-term results using VAR/VECM. At the short-term level, competition did not significantly affect stability, while stability had a more significant effect on competition. However, increased competition seems to improve banking stability in the long run. The role of allowance of impairment losses varies depending on the period, with its negative impact on stability in the short-term. This study uses loan loss provision (LLP) as a moderating variable to examine the extent to which competition enhances stability. Internal banking policies must strengthen understanding of the impact of loan loss provisions and ensure effective risk management practices. In addition, banks must consider long-term strategies in managing competition by maintaining a balance between healthy competition and sound risk management to achieve long-term stability.